Pemberhentian Tidak Dengan Hormat Anggota Kepolisian Negara Republik Indonesia - Rido Leiwakabessy; Jemmy Jefry Pietersz; Renny Heronia Nendissa (Faculty of Law, Universitas Pattimura, 2023)
Introduction: Disrespectful dismissal of members of the Indonesian National Police must be in accordance with the provisions of the legislation.Purposes of the Research: Therefore, this paper aims to examine and analyze the validity of dishonorable dismissal and legal remedies that can be taken. Methods of the Research: The research method used is normative juridical, using a statutory approach and a conceptual approach. The legal materials used in this study are primary legal materials and secondary legal materialsResults of the Research: The recommendation for dishonorable discharge issued by the Commission for the Professional Code of Ethics of the Indonesian National Police to the violator, namely Markus Junus Pattimaipau, as the basis for the issuance of a decree by the Maluku Regional Police Chief regarding Disrespectful Dismissal is not in accordance with the mechanism of the provisions of the applicable laws and regulations. Apart from that, the recommendation for dishonorable dismissal that is issued if it is related to the legal requirements of a decision does not meet the requirements of the procedure and substance and general principles of good governance, then the decision can be said to have no validity. The issuance of the Decree of the Head of the Maluku Regional Police regarding the dishonorable discharge of the Indonesian National Police Service which has no further validity. Markus Junus Pattimaipau in the aspect of legal protection who is harmed by the State Administrative Decree may file legal remedies based on the provisions of the applicable laws and regulations.